UN Sanctions Against Iraq: From Ailment to Chronic - Khalid Manzoor Butt* Anam Abid Butt (Journal of Political Studies, 2014)
Sanctions are penalties or restrictions imposed by a state, group of states or an international organization on another state, usually involved in the act of international delinquency, to compel that state to amend its behaviour or to change its conduct or policies. At present, sanctions have become an important tool of coercion which the United Nations (UN) applies against states that are indulged in threatening of international law or peace and established international norms. However, these measures can have immense effects for the targeted state and its population as a whole. The UN sanctions imposed on Iraq from 1990 to 2003 are considered the most comprehensive and effectively enforced sanctions. This case is an example of the grave cost in human suffering that sanctions can exert on a country which turns into almost a breakdown in economic, social and political structures. Due to its effects on Iraqi populace, UN sanctions tool has earned huge criticism from many commentators, stakeholders and international elites. An account will be provided of the effects of thirteen years long UN sanctions on Iraq and causing factors. During this thirteen years period, a criminal silence on the part of Organization of Islamic Conference (OIC), Arab League and international community has been observed. Russia and China, the permanent members of the Security Council (SC), were not more than spectators during the period for some dubious reasons. The UN, the most prestigious international organization, strengthened the perception that it was a porous body and played a second fiddle to the U.S. It cannot be rejected that UN has been mostly protecting the interests of powerful nations. Furthermore, efforts would be made to figure out some useful recommendations for the improvement of UN sanctions mechanism so that the sufferings of the sanctioned society could be reduced in future sanctions regimes.